L’ analyse empirique de l’impact de la politique monétaire sur la bourse des valeurs au Maroc : Un essai à l’aide d’un modèle vectoriel autorégressif (VAR) - KHARBOUCH, OMAR; OUASKOU, Hamid (Revue du contrôle, de la comptabilité et de l’audit, 2024)
The global importance of central banks in navigating financial crises and economic fluctuations has been underscored (Lorenzoni, 2015). The pivotal role of the institution overseeing monetary policy in shaping both the term structure of interest rates and stock market dynamics is evident. Economic theory posits a direct link between money and prices, with an increase in the money supply leading to proportional inflation, and vice versa (Dées, 2019). Keynesian perspectives, emphasizing nominal rigidities and long-term money neutrality, assert that a rising money supply influences the real economy through interest rate reduction. This dual impact of money on economic agents remains underexplored quantitatively in the Moroccan context. This study aims to fill this gap by introducing a novel quantitative framework. Employing a Vector Autoregression (VAR) model with simultaneous equations, the research assesses the short and long-term causality between central bank decisions, expressed as cyclical variables, and the stock market’s performance. The analysis aims to elucidate the directional impact of monetary policy on asset returns and prices in the Moroccan context.